Zambia’s Ministry of Green Economy and Environment pursues peace and security for green growth - Pacillo, Grazia; Gadeberg, Marianne; Maviza, Gracsious; Caroli, Giulia (2025)
In 2024, the CGIAR Research Initiative on Climate Resilience (ClimBeR) collaborated with local communities and national stakeholders, informing Zambia’s National Green Growth Strategy 2024-2030. Consequently, the strategy now includes social cohesion, peace, and stability as guiding principles for green growth. It emphasizes enhancing institutional capacity as a key enabling condition, and it includes provisions for research and training on climate, peace, and security. The Green Growth Strategy aims to foster a low-carbon and socially inclusive economy by 2030.